The Influence of Financial Literacy, Lifestyle and Fintech Usage on The Consumer Behavior of Generation Z in Bajo Subdistrict - A. Asmita; A. Asriany; H. Hapid (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of financial literacy, lifestyle, and fintech usage on consumer behavior among Generation Z in Bajo District. This study employed a quantitative approach involving 96 Generation Z respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The findings indicate that financial literacy has a positive and significant effect on consumer behavior among Generation Z. Individuals with higher levels of financial literacy are better able to manage their finances and regulate their spending behavior. Lifestyle also has a positive and significant effect on consumer behavior, indicating that a more consumer-oriented lifestyle increases the tendency to engage in consumption activities. Meanwhile, fintech usage does not have a significant effect on consumer behavior, as most respondents use fintech primarily for general transaction purposes.